Migration and Mental Health : Evidence from a Natural Experiment - Stillman, Steven; McKenzie, David; Gibson, John (World Bank, Washington, DC, 2012)
People migrate to improve their well-being, whether through an expansion of economic and social opportunities or a reduction in persecution. Yet a large literature suggests that migration can be a stressful process, with potentially negative impacts on mental health, reducing the net benefits of migration. However, to truly understand the effect of migration on mental health one must compare the mental health of migrants to what their mental health would have been had they stayed in their home country. The existing literature is not able to do this and typically settles for comparing the mental health of migrants to that of natives in the destination country, which takes no account of any pre-existing differences between these groups. This paper overcomes the selection problems affecting previous studies of the effect of migration on mental health by examining a migrant lottery program. New Zealand allows a quota of Tongans to immigrate each year with a lottery used to choose among the excess number of applicants. A unique survey conducted by the authors in these two countries allows experimental estimates of the mental health effects of migration to be obtained by comparing the mental health of migrants who were successful applicants in the lottery to the mental health of those who applied to migrate under the quota, but whose names were not drawn in the lottery. Migration is found to lead to improvements in mental health, particularly for women and those with poor mental health in their home country.